Coronary sinus electrogram characteristics predict termination of AF with ablation and long‐term clinical outcome. (28th July 2022) - Honarbakhsh, Shohreh; Schilling, Richard J.; Keating, Emily; Finlay, Malcolm; Hunter, Ross J.
Abstract: Introduction: Markers predicting atrial fibrillation (AF) termination and freedom from AF/atrial tachycardia (AT) has been proposed. This study aimed to evaluate the role of novel coronary sinus (CS) electrogram characteristics in predicting the acute ablation response and freedom from AF/AT during follow‐up. Methods: Patients undergoing ablation for persistent AF as part of the Stochastic Trajectory Analysis of Ranked signals mapping study were included. Novel CS electrogram characteristics including CS cycle length variability (CLV) and CS activation pattern stability (APS) and proportion of low voltage zones (LVZs) were reviewed as potential predictors for AF termination on ablation and freedom from AF/AT during follow‐up. The relationship between localized driver characteristics and CS electrogram characteristics was also assessed. Results: Sixty‐five patients were included. AF termination was achieved in 51 patients and 80% of patients were free from AF/AT during a follow‐up of 29.5 ± 3.7 months. CS CLV of <30 ms, CS APS of ≥30% and proportion of LVZ < 30% showed high diagnostic accuracy in predicting AF termination on ablation and freedom from AF/AT during follow‐up (CS CLV odds ratio [OR] 25.6, area under the curve [AUC] 0.91; CS APS OR 15.9, AUC 0.94; proportion of LVZs OR 21.4, AUC 0.88). These markers were independent predictors of AF termination on ablation and AF/AT recurrence during follow‐up. Ablation of a smaller number of drivers that demonstrate greater dominance strongly correlate with greater CS organization. Conclusion: Novel CS electrogram characteristics were independent predictors of AF termination and AF/AT recurrence during follow‐up. These markers can potentially aid in predicting outcomes and guide ablation and follow‐up strategies.